2011
DOI: 10.1007/s00423-011-0824-5
|View full text |Cite
|
Sign up to set email alerts
|

Superior mesenteric artery first combined with uncinate process approach versus uncinate process first approach in pancreatoduodenectomy: a comparative study evaluating perioperative outcomes

Abstract: SMA first is a safe technique. It compares well with the uncinate first approach in terms of operative time, blood loss, number of lymph nodes retrieved, margin positivity and operative morbidity. Both techniques may be useful in situations such as a large uncinate process tumor or when superior mesenteric vein/portal vein/superior mesenteric artery involvement is suspected or present. Further studies, evaluating data related to specific predefined uncinate tumors, would be the next logical step in further def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…Previously, Shukla et al [17] described the dissection of the uncinate process from the mesenteric vessels, facilitating tumor removal and demonstrating the involvement of these vessels early during surgery. This approach is recommended in uncinate tumors and in cases with suspected involvement of the SMV or SMA [2] . Another advan-tage of this approach is the early ligation of the IPDA, but it does not allow early identification of an anomalous RHA [9] .…”
Section: Right/medial Uncinate Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, Shukla et al [17] described the dissection of the uncinate process from the mesenteric vessels, facilitating tumor removal and demonstrating the involvement of these vessels early during surgery. This approach is recommended in uncinate tumors and in cases with suspected involvement of the SMV or SMA [2] . Another advan-tage of this approach is the early ligation of the IPDA, but it does not allow early identification of an anomalous RHA [9] .…”
Section: Right/medial Uncinate Approachmentioning
confidence: 99%
“…Figueras et al [3] compared classical PD with the posterior artery-first approach, reporting a reduction in complications and hospital stay, while Dumitrascu et al [1] found no significant differences in hospital stay, early morbidity, mortality, or overall survival. Shrikhande et al [2] compared classical PD with the "uncinate artery-first approach" and found no evidence of significant differences in blood loss, operative time, margin involvement, lymph node yield, or complications.…”
Section: Superior Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical steps are achieving a negative retroperitoneal margin and re-establishing pancreatoenteric continuity minimizing postoperative pancreatic leak risk [1][2][3][4]. Aiming at increasing the rate of R0 resection during pancreatoduodenectomy, many experienced teams have recommended the superior mesenteric artery (SMA)-first approach, consisting in early identification of the SMA at its origin, with further resection guided by SMA anatomic course [5][6][7][8][9]. We describe our technique of LPD with SMAfirst approach and pancreatogastrostomy assisted by minilaparotomy.…”
mentioning
confidence: 98%
“…6,7 Recently, several procedures for artery-first approaches such as posterior, uncinated, and mesenteric approach have been introduced for improving perioperative outcomes such as curability and decreasing blood loss and morbidity. [8][9][10][11] Incidentally, it has been well known that early ligation of the inferior pancreaticoduodenal artery (IPDA)-one of the efferent arteries of the pancreas head-considerably reduces intraoperative bleeding and postoperative complications. [12][13][14] Owing to the various anatomic origins of IPDA, identification is difficult in some patients.…”
mentioning
confidence: 99%